Impact of conservation agriculture and resource conservation technologies on carbon sequestration–a review - PATLE, G T; BANDYOPADHYAY, K K; SINGH, D K (The Indian Journal of Agricultural Sciences, 2013)
Global warming and its consequences are amongst the most serious problems of the present century. Increase in concentration of greenhouse gases (GHGs) in the atmosphere is major cause for global warming. Increase in global concentration of CO2 is mainly due to fossil fuel consumption, land use change and soil cultivation. Methane and N2Oconcentrations are increasing primarily due to dairy and agriculture. Sequestering atmospheric carbon in agricultural soils may partially offset the emission of greenhouse gases from fossil fuel consumption. Conservation agriculture helps in sequestering atmospheric carbon in soil-plant system through change in agricultural operations and management practices. Conservation tillage along with efficient management of inputs, viz. irrigation, fertilizer and pesticides facilitates carbon sequestration in soil-plant system. Land use change and conventional agricultural practices are major contributors to global annual emission of CO2. Conservation agriculture and recommended management practices (RMPs) collectively are helpful to offset part of the emissions due to unscientific agricultural practices. In India, agriculture contributes about 17 per cent of the country’s total GHGs emission. An intensive agricultural practice during the post-green revolution era without caring for the environment has supposedly played a major role towards enhancement of the greenhouse gases. Due to increase in demand for food production the farmers have started growing more than one crop a year through repeated tillage operations using conventional agricultural practices. Increase in carbon emission is the major concern, which is well addressed in kyoto protocol. Nowadays, more emphasis has been given for promotion of conservation agriculture to mitigate the impact of climate change.